MENINGKATKAN HASIL BELAJAR SISWA PADA MATAPELAJARAN IPS DENGAN METODE MIND MAPPING - Sari, Maya Kartika (Premiere Educandum, 2012)
Social science has been viewed as naturally theoretic, which requires students to memorize all learned materials. The learning experience will be stucked in freez learning atmosphere when the teacher traditionally preeches and dictates against the students, as the teacher-centered approaches have run. This model of teaching produces passive students with low acheivement. In effort of dveloping the vivid learning experience, variative models of teaching must be applied by the teacher. Through this research, the researcher proposes Mind Mapping Teaching Method, hopping that the the students learning activities and achievement can be developed. Mind mapping teaching method can tentatively encourage student to be active, innovative, creative and imaginative along the way with the learning process. The application of mind mapping teaching method can hopefully develop students learning activities and achievement through the given action research design.Key words: Learning achievement, Mind Mapping Method, Social Science